Higher dietary vitamin D intake influences brain and mental function in elderly Americans: a cross-sectional analysis - Chen, Huizhen; Pang, Xing; Huang, Yinhui (Frontiers in Nutrition, 2025)
BackgroundVitamin D is known to have a potential impact on cognitive function and mental health. This study aims to assess the association between dietary vitamin D intake and cognitive performance, as well as depression, in an elderly U.S. population.MethodsData from the National Health and Nutrition Examination Survey (NHANES) 2013–2014 were analyzed. A total of 1,344 elderly participants were categorized into three tertiles based on their dietary vitamin D intake (D2 + D3). Cognitive function was measured using the Consortium to Establish a Registry for Alzheimer’s Disease (CERAD) test, Digit Symbol Substitution Test (DSST), and Animal Fluency Test, while depression was assessed through the Patient Health Questionnaire-9 (PHQ-9). Adjustments were made for confounding variables, including age, sex, race, education, physical activity level, and other dietary factors.ResultsAfter adjustment for confounders, individuals in the 3rd tertile of vitamin D intake (≥4.9 mcg/day) had significantly reduced odds of low performance on the CERAD test (OR: 0.77, 95% CI: 0.57–0.98; p = 0.031) and Animal Fluency test (OR: 0.63, 95% CI: 0.49–0.85; p = 0.013) compared to the 1st tertile of intake (≤2.4 mcg/day). Similarly, participants in the 3rd tertile of vitamin D intake had lower odds of depression (PHQ-9 score > 4) after adjustment (OR: 0.68, 95% CI: 0.48–0.99; p = 0.046).ConclusionOur findings suggest that dietary vitamin D intake is associated with improved cognitive function and depressive symptoms in elderly individuals. However, further longitudinal studies are needed to establish causality and explore the underlying mechanisms.